A new species of Moina Baird, 1950 (Crustacea: Anomopoda) from Socotra Island, Yemen - van Damme, Kay; Dumont, Henri J. (Zootaxa, 2008)
We describe a new species, Moina diksamensis n. sp., endemic to Socotra Island, Yemen, including details of important limb characters not usually described in the literature. Moina diksamensis has a peculiar ecology and is found in close association with freshwater crabs of the genus Socotra Cumberlidge & Wranik, 2002. The new species is closely related to M. mukhamedievi Mirabdullaev, 1998 from Uzbekistan, another biogeographical link for freshwater crustaceans between this Afro-Arabian island and Asia.